1990
DOI: 10.1097/00000658-199008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Radical Pancreatectomy for Pancreatic Cancer in the Elderly

Abstract: Surgical resection provides the only potential cure for pancreatic cancer, yet resection in patients 70 years of age and older remains controversial because of presumed increased morbidity and mortality. Our aim was to determine the operative results in patients 70 years of age or older undergoing potentially curative radical pancreatic resection for pancreatic cancer from 1982 through 1987. Of 206 consecutive patients explored for potential resection, 42 patients (mean age, 75 years) had potentially curative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 12 publications
3
26
0
1
Order By: Relevance
“…Specialized units can achieve operative mortality rates below 5%, morbidity rates below 30%, and hospital stays in the region of 2 or 3 weeks. Even the elderly can be operated on with comparable outcome [15][16]. A Bill roth-1-type reconstruction as used in the present series, with the biliary anastomosis in the natural position 4-5 cm distal to the duodenojejunal anastomosis, was first described by Watson [17], The excellent functional and physiological results of this method of restoration of gas trointestinal continuity after pancreaticoduodenectomy have been confirmed by others [18][19][20].…”
Section: Discussionmentioning
confidence: 58%
“…Specialized units can achieve operative mortality rates below 5%, morbidity rates below 30%, and hospital stays in the region of 2 or 3 weeks. Even the elderly can be operated on with comparable outcome [15][16]. A Bill roth-1-type reconstruction as used in the present series, with the biliary anastomosis in the natural position 4-5 cm distal to the duodenojejunal anastomosis, was first described by Watson [17], The excellent functional and physiological results of this method of restoration of gas trointestinal continuity after pancreaticoduodenectomy have been confirmed by others [18][19][20].…”
Section: Discussionmentioning
confidence: 58%
“…Some studies have shown that for resectable pancreatic carcinoma, pancreatic resections can be performed for the elderly with acceptable morbidity and mortality rates and possible long-term outcome [17,18,19,20,21,22,23,24,25]. However, in locally advanced pancreatic carcinoma treated with chemoradiotherapy, the tolerability, efficacy of treatment and long-term outcome have not been discussed extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity and mortality rates in patients older than 70 years are slightly higher (31 percent and nine percent, respectively), but still acceptable. 31 The pylorus-preserving pancreaticoduodenectomy (PPPD) has received considerable attention recently. PPPD differs from the classic pancreaticoduodenectomy in that the entire stomach including the pylorus and a 2-to 3-cm cuff of proximal duodenum are preserved.…”
mentioning
confidence: 99%
“…Reported actuarial five-year survivals after curative resection have generally been dismal regardless of the type of resection performed, averaging about five to 10 percent. 25,31,37 Recently, however, several centers have reported encouraging results with markedly improved actuarial five-year survivals after curative resection approaching 20 to 25 percent. 26,27,38 The reasons for these improved results are unknown, but may be related to factors such as better preoperative staging, improved operative techniques and postoperative adjuvant chemoradiation therapy, inaccurate histology (e.g., misidentification of islet cell tumor or fibrosing pancreatitis), or to a change in tumor biology.…”
mentioning
confidence: 99%